Gender in the Eyes of the Indonesian Muslim Organizations - Ropi, Ismatu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
Needles to say that there are numerous Muslim organizations all over Indonesia, and therefore, some limitation is a necessity. The following qualifications are used to select which of them are to be included: (1) they must be well established and enjoyed a high community support, and (2) act as centers of religious values production and reproduction, especially for the surrounding community. Thus only Muslim organizations with real mass support and strong networks, as well as with real contributions in shaping the Muslims minds and attitudes, will be studied. Using the criteria, besides PERTI, NU and Muhammadiyah mentioned before, thirteen organizations are selected including PERSIS, DDI (Darul Dakwah wa lrryad), Nahdlatul Wathan, and al-Washliyah. Some of these organization are strong only outside Java sucb as PERTI in West Sumatera, al-Washliah in North Sumatera and DDI in South Sulawesi. It is only natural that the research also put great emphasis on Muslims traditions outside Java.DOI: 10.15408/sdi.v9i2.671